UPAYA PENINGKATAN PRODUKSI MENTIMUN (Cucumis sativus L) MELALUI WAKTU PEMANGKASAN PUCUK DAN PEMBERIAN PUPUK POSFAT - Ubad Badrudin; Syakiroh Jazilah; Ari Setiawan (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2011)
The experimental design used was randomized complete block design. The first factor is time pruning consist of without pruning apical (W1), pruning time during the vegetative phase of the age of 14 HST (W2), and the pruning phase of generative shoots at age 21 HST (W3), whereas the second factor is composed of phosphate fertilizer from without phosphate fertilizer (P0), 75 kg of phosphate fertilizer / ha (P1), phosphate fertilizer 150 kg / ha (P2), and phosphate fertilizers 225 kg / ha (P3). Data analysis by F test and if thereare significant differences followed by DMRT test and orthogonal contrasts. Variables observed were samples of plant height per plant, number of leaves per plant sample, wet weight of sample plants per plant, plant dry weight per plant samples, flowering, fruit number per plant sample, the sample length of the fruit per plant, weight of fruit per plant sample, wet weight of plants per plot effectively, and dry weight of plants per plot effective. The results showed that the timing of pruning shoots were significantly different to all the observed variables, except variable flowering, while phosphate fertilizer were significantly against all variable. There is interaction between time of pruning shoots and phosphate fertilizers to the plant height per plant sample, the number of leaves per plant sample, wet weight of sample plants per plant, plant dry weight perplant sample, weight of fruit per plant sample, wet weight of plants per plot effectively, and dry weight of plants per plot effective  Key words: cucumber, shoot pruning, fertilizer phosphate